Inclusion or Exclusion of External Voices in Decision-Making on the EU Regulation on Deforestation-Free Products (EUDR): Heard, but Not Listened To - Alons, Gerry; Zwaan, Pieter (Revue Interventions économiques / Papers in Political Economy, 2026)
Over the last years the EU has taken a more unilateral approach in linking sustainable development to trade by adopting legislation that affects the sustainable production and trade of products within and beyond its internal market. One of these laws is the EU Deforestation Regulation (EUDR). By many, the adoption of the EUDR has been hailed as a successful linkage between sustainability and trade, and an important step in countering deforestation. Others, however, have criticized the policy making process and the limited possibilities it offered to engage with certain stakeholders and their concerns. Drawing on various theories of the policy process, this article sheds light on processes of exclusion and inclusion during the policymaking process of the EUDR. We show that political opportunity structures mediate the impact of stakeholder mobilization, with their institutional dimensions affecting access to policymakers and their discursive dimensions influencing policymakers' receptiveness to different arguments. We show how exclusion instead of inclusion contributed to stronger or more developed environment-trade linkage in the case of the EUDR.